1997
DOI: 10.1021/la970135r
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Alkylsiloxane Self-Assembled Monolayers on the Oxidized Si(100) Surface

Abstract: The thermal behavior of alkyltrichlorosilane (CH3(CH2)n-1SiCl3) based self-assembled monolayers on the oxidized Si(100) surface has been examined under ultrahigh vacuum conditions for n ) 4, 8, and 18. Using high-resolution electron energy loss spectroscopy and contact angle analysis, it is found that the monolayers are stable in vacuum up to about 740 K independent of chain length. Above 740 K the chains begin to decompose through C-C bond cleavage, resulting in the desorption of hydrocarbon fragments. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
131
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 32 publications
11
131
4
Order By: Relevance
“…These results agree with Ref. 19 where degradation of ODTMS SAMs on oxidized silicon ͑100͒ surfaces was found between 740 K and 815 K and assigned to cleavage of C-C bonds. For C 4 H 9 fragment ͑57 amu͒ a minor peak at T 1 = 650 K is observed for reference and ODTMS-modified surfaces.…”
supporting
confidence: 93%
“…These results agree with Ref. 19 where degradation of ODTMS SAMs on oxidized silicon ͑100͒ surfaces was found between 740 K and 815 K and assigned to cleavage of C-C bonds. For C 4 H 9 fragment ͑57 amu͒ a minor peak at T 1 = 650 K is observed for reference and ODTMS-modified surfaces.…”
supporting
confidence: 93%
“…Maboudian et al have reported on the thermal degradation behavior in vacuum of OTS [36] and FDTS [37] on oxidized surfaces. They found that OTS coatings are stable in vacuum up to 467…”
Section: Fdts Fots Fomds Fomms Fotesmentioning
confidence: 99%
“…Silylation, also known as silane grafting, has been proven to be an efficient method to modify inorganic materials [1][2][3][4]. Comparing with surfactant intercalation, silylation enables a durable immobilization of the organic moieties by forming covalent bonds between silane and substrates.…”
Section: Introductionmentioning
confidence: 99%